From first to third stream activities in higher education: the case of the Spanish Defence University centre. Issue 3 (3rd July 2019) - Callado-Muñoz, Francisco José; Utrero-González, Natalia
ABSTRACT: The paper adds to the debate on the relationship between military spending and economic growth by analysing the contribution of a military university centre to regional economic development. It goes beyond traditional economic impact studies by including research related effects and integrating "third stream" activities. Conceptualization and categorization are carried out to thoroughly analyse the different dimensions of knowledge and "third stream" actions. The analysis is performed from its settlement and during its first 5 years of existence which allows showing how the strategy of community engagement is developed. The conclusion suggests that, as traditional military roles extend, and military education institutions become higher education institutions, a comprehensive evaluation should be taken into account to enrich the public debate on government spending.